(untitled) - Jiřičková, Jiřina (Aura musica, 2019)
The paper is based on vocal activities used in the workshop entitled "Playfully with Voice", which took place during the Music Conference for the 3rd Millennium on April 6, 2019. Preparatory singing exercises complement the physical activities that help children to relax. These exercises require children's attention and follow mostly multiple intentions. They allow children to search for their voice and to manifest themselves naturally.